Determination of sucralose in light nectars by HPLC-RI - Kimura, Iracema A. (2007)
This paper describes a methodology for performing the sucralose determination in light nectar samples, by using solid phase extraction (SPE) and HPLC with refractive index detection. Fourteen samples of grape, peach, strawberry, mango, guava and passion fruit light nectars from different manufacturers were centrifuged at 3000rpm and cleaned up on C18 SPE cartridges (500mg, 3mL). The detection and quantification limits were 1.7mg. 100mL-1 and 5.9mg.100mL-1, respectively, and the recoveries of sucralose were satisfactory, being around 100%. The matrix effect correction was needed for light grape nectars only. The simplicity of the presented method, the minimal solvent volume requirements, and the easiness in extracting many samples at the same time make this methodology suitable for laboratory routine analyses.